Britain in agony - "Clutterbuck, Richard" (London, 1978)
Most of the research for this book was done in 1976-7 with the support of a grant from the Wolfson Foundation which provided me with a research assistant; the book also incorporates some earlier done on the incidents at Saltley, Shrewsbury and Red Lion Square in 1974-5 under a Social Science Research Council grant.
Keywords: Public Administration